2006
DOI: 10.1007/s10495-006-5396-4
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of hyaluronan binding protein 1 (HABP1/p32/gC1qR) is associated with Cisplatin induced apoptosis

Abstract: We have earlier reported that overexpression of HABP1 in fibroblast cells causes perturbed cell growth, extensive vacuolation and restricted entry to the S-phase, finally leading to apoptosis (Biochem Biophys Res Commun 2003; 300: 686-693). In the present study, we investigate the regulation of HABP1 expression in cisplatin induced apoptosis in HeLa cells. Apoptosis induced in HeLa cells at 24 h of cisplatin treatment was confirmed by nuclear fragmentation, increase in subdiploid population and the enhanced ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 47 publications
3
39
0
Order By: Relevance
“…Previous studies have shown that silencing of p32 reduced cisplatin-, harakiri-, and p14ARF-p16INK4a locusinduced apoptosis (21,22,25). Similarly, we found that p32 silencing conferred protection against UV-induced apoptosis.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Previous studies have shown that silencing of p32 reduced cisplatin-, harakiri-, and p14ARF-p16INK4a locusinduced apoptosis (21,22,25). Similarly, we found that p32 silencing conferred protection against UV-induced apoptosis.…”
Section: Discussionsupporting
confidence: 84%
“…Reducing the levels of p32 in mammalian cells has been shown to make them more resistant to apoptosis (21,22), suggesting that p32 has a proapoptotic activity. Consistent with these data, when p32 levels were reduced using siRNA ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Xiao and co-workers published a study in 2014 showing that mitochondrial p33 is pro-apoptotic and regulates mitochondrial calcium up-take [41], whereas Watthanasurorot and collaborators employ an arthropod model to demonstrate that binding of cytosolic p33 to calreticulin protects cells from dying [42]. While the molecular mechanisms are not completely understood, it appears that shuttling of p33 between the cytosol and mitochondria or the nucleus is essential in these processes [42,43]. Dual or multifold intracellular targeting of proteins with specific localization sequences is an emerging field of research [44,45] and several mechanisms have been proposed to explain this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its predominant localization to the matrix of mitochondria, p32 is also found in the nucleus and at the plasma membrane. Due to its receptor function for the C1q component of complement, p32 is also known as gC1q-R (21). This evolutionarily conserved protein interacts with several cellular proteins with diverse functions, e.g., splicing factor SF2, the proapoptotic BH3-only protein Hrk, and also viral proteins, such as hepatitis C virus core protein and human immunodeficiency virus Rev protein (20).…”
mentioning
confidence: 99%